MEDICAL IMAGE REGISTRATION: BASIC SCIENCE AND CLINICAL IMPLICATIONS - Imran, Muhammad Babar; Meo, Sultan Ayoub; Yousuf, Mohammad; Othman, Saleh; Shahid, Abubakar (Journal of Ayub Medical College Abbottabad, 2010)
Image Registration is a process of aligning two or more images so that corresponding feature can be related objectively. Integration of corresponding and complementary information from various images has become an important area of computation in medical imaging. Merging different images of the same patient taken by different modalities or acquired at different times is quite useful in interpreting lower resolution functional images, such as those provided by nuclear medicine, in determining spatial relationships of structures seen in different modalities. This will help in planning surgery and longitudinal follow up. The aim of this article was to introduce image registration to all those who are working in field of medical sciences in general and medical doctors in particular; and indicate how and where this specialty is moving to provide better health care services. Keywords: Medical imaging, Image processing, Image registration, Image fusion, Hybrid imaging, Automation, Robotic medical intervention